The efficacy and safety of topical 10% potassium hydroxide for molluscum contagiosum: a systematic review and meta-analysis. (3rd April 2022) - Heo, Jae Young; Park, Tae Heum; Kim, Woo Il
Abstract: Background: Molluscum contagiosum (MC) is a self-limited cutaneous viral infection. Topical 10% potassium hydroxide (KOH) has been used for treating MC. However, it remains unclear whether it is beneficial or not to apply topical 10% KOH for treating MC. Methods: To confirm the efficacy and safety of topical 10% KOH compared with placebo as well as other treatments for MC, meta-analysis was used. Up to September 2020, we performed a comprehensive search of literature based on three databases with following keywords including 'molluscum contagiosum' and 'potassium hydroxide'. Results: Our meta-analyses demonstrated a significant difference between topical 10% KOH and placebo for complete clearance of MC (RR: 2.96, 95% CI: 1.69 − 5.17, p  = .0001), while there were no statistical differences between them in the number of patients with adverse events (RR: 1.73, 95% CI: 0.67 − 4.45, p  = .2562). Also, topical 10% KOH was as effective as mechanical treatments for MC (RR: 0.95, 95% CI: 0.84 − 1.07, p  = .3833). Conclusion: We demonstrate that application of topical 10% KOH may be one of effective and appropriate methods for the treatment of MC compared with awaiting spontaneous resolution due to its safety and effectiveness.